Duplicated tramadol use in chronic low back pain: A nationwide cross‐sectional study. Issue 3 (8th October 2019) - Koo, Hyunji; Lee, Min Taek; You, Seung Hun; Seon, Jeong Yeon; Lee, Sieun; Jeong, Kyeong Hye; Jung, Sun‐Young
Abstract: Tramadol is a weak opioid that is commonly used for chronic low back pain (LBP). Despite its effectiveness, duplicated use of tramadol, which may indicate abuse or dependence, may exacerbate potential adverse reactions. This population‐based, cross‐sectional study aimed to investigate the prevalence of duplication of tramadol and its associated factors among patients with LBP. From a Korean nationwide claims database, non‐hospitalized patients aged 40‐99 years with LBP without malignancy were prescribed tramadol during 2014‐2016. Duplication of tramadol was defined as overlapping of prescription days. Among them, we defined "extensive duplication (ED)" when days of tramadol duplication cover 10% or more of the days prescribed tramadol. Patient and healthcare utilization factors associated with ED were examined using a logistic regression model. The study population was 6 417 503 patients. Of these, 13.7% were ED users. The age‐ and sex‐standardized prevalence of using tramadol twice or more a year was 14.06 per 100 people in 2014, 13.74 per 100 people in 2015 and 13.52 per 100 people in 2016. ED occurred more in those in the group aged 70‐79 years (OR 1.12, 95% CI 1.11‐1.13) than 40‐49 years and in those with comorbidities, such as drug abuse (OR 2.99, 95% CI 2.05‐4.36) or depression (OR 1.75, 95% CI 1.72‐1.77). Based on the results of this study, a proper management system is needed to avoid tramadol duplication among older people and patients with drug abuse or depression.